1978
DOI: 10.1159/000198089
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Inhibition of Secretin and Combined Secretin and Cholecystokinin Stimulated Pancreatic Exocrine Secretion in Health and Disease

Abstract: The effect of glucagon infusion on secretin and combined secretin and cholecystokinin stimulated exocrine pancreatic secretion was studied in normal subjects and in patients after acute and with chronic pancreatic disease. Glucagon inhibited pancreatic protein secretion and had no inhibitory effect on volume or bicarbonate secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…In dog pancreas, glucagon mainly inhibits water and bicarbonate secretion in response to a meal (Singer et al 1978). However, results of studies conducted on human subjects are contradictory (Fontana et al 1975;Clain et al 1978). Presently, it is impossible to establish whether these effects are due to the direct binding of glucagon to duct cells or to a modulating action exerted on the pancreatic nervous system.…”
Section: Islet Influence On Pancreatic Duct Secretionmentioning
confidence: 99%
“…In dog pancreas, glucagon mainly inhibits water and bicarbonate secretion in response to a meal (Singer et al 1978). However, results of studies conducted on human subjects are contradictory (Fontana et al 1975;Clain et al 1978). Presently, it is impossible to establish whether these effects are due to the direct binding of glucagon to duct cells or to a modulating action exerted on the pancreatic nervous system.…”
Section: Islet Influence On Pancreatic Duct Secretionmentioning
confidence: 99%
“…On the one hand, an inhibition of the exogenously or endogenously stimulated volume and enzyme secretion has been observed in animals [16,23,34] and in man [4,6,14]. On the other hand, an increase in these parameters was also noted [21,23,26].…”
Section: Discussionmentioning
confidence: 95%
“…The conflicting observations concerning the effect of acetylcholine [9,13,22,27,31], gastrin [3,5,11,12,24,28,30,32], and glucagon [4,6,14,16,21,23,26,34] on the pancreas may be caused by the fact that these conditions were not or only partly fulfilled. Therefore, this study was directed to determine the action of these stimuli given alone or in combination with secretin (S) and cholecystokinin (CCK) in the isolated perfused pancreas and by use of dose-response curves.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of glucagon on exocrine secretion has not yet been fully elucidated. Some studies have demonstrated inhibitory effects of glucagon on secretin- and cholecystokinin-stimulated pancreatic protein but not on bicarbonate secretion 5 , 6 , others showed that glucagon inhibits both postprandial protein and bicarbonate secretion 5 , 7 . However, more recent studies indicate that the effect of glucagon on isolated pancreatic acini appears to be direct and stimulatory, instead of inhibitory, suggesting complex action at the cellular versus physiological levels, with the inhibitory effects perhaps involving somatostatin release 5 , 8 .…”
Section: Introductionmentioning
confidence: 99%